Improvement of The Ability of Mathematical Creative Thinking through Pace-Geogebra Learning in Terms of Student Self-Regulated Learning - Yulianti, Nurendah; Septian, Ari; Sugiarni, Rani (PRISMA, 2025)
The ability of mathematical creative thinking is essential for students to possess, but in reality, the level of mathematical creativity in Indonesia remains comparatively low. This study aims to find out if learning with PACE-GeoGebra helps improve students' mathematical creative thinking abilities and to understand how self-regulated learning relates to the improvement of these abilities through PACE-GeoGebra. Quasi-experimental research methodology is employed. The study uses a non-equivalent comparison group design. All of the 10th graders enrolled in one of Cianjur's high schools for the 2024–2025 school year make up the study's population. Two classes—classes X-E and X-F—were chosen as samples from the population using a purposive sampling technique. While the control group employed the standard learning model, the experimental group employed the PACE-GeoGebra learning model. Tests and questionnaires with information on quadratic functions were the tools utilized. Using the two-sample mean equality test, data analysis was done on the average gain index between the two sample classes. The research results show that (1) there is a significant difference in the improvement of mathematical creative thinking abilities between students who use the PACE-GeoGebra approach and students who use conventional learning. (2) There is a correlation between student self-regulated learning and the improvement of mathematical creative thinking skills through PACE-GeoGebra learning.